Behavior of physiological variables during a water gymnastics class in women - Mabel Micheline Olkoski; Dalila Tosset; Marcelo Diederichs Wentz; Silvana Corrêa Matheus (Universidade Federal de Santa Catarina, 2010)
The aim of this study was to analyze the behavior of physiological variables and rating of perceived exertion (RPE) during the different phases of a water gymnastics class. Seventeen female university students (age: 23 ± 3.5 years) were evaluated in two steps: 1) incremental treadmill test (peak VO2 and HRmax); 2) assessment of body composition and achievement in the water gymnastics class (HR, VO2, [lac], and RPE). Descriptive statistics and repeated measures ANOVA with the post hoc Student-Newman-Keuls were used (p< 0.05). The results showed that both HR and VO2 differed significantly (p=0.000) between the three phases of the class. Blood lactate only differed significantly (p=0.001) between the early (1.55 mM) and the main phase (3.58 mM). The mean RPE was 11 and total calorie expenditure was 262.10 kcal. In conclusion, the physiological variables studied and RPE vary significantly according to the phase of the water gymnastics class. In addition, the intensity of effort (HR, VO2 and [lac]) obtained for the main phase is within the parameters established in the literature for aerobic exercise. Thus, regular water gymnastics classes with this structure may improve the physical condition of young adult women.